An Interdisciplinary Look at The Comparative Examination of Physics and Chemistry Coursebooks - Sevim Bezen; Ceren Başal; Işıl Aykutlu; Nilgün Seçken; Celal Bayrak (Anı Publishing, 2018)
In the study, the aim was to examine comparatively the subjects in the physics and chemistry course books, which are designed in accordance with the physics and chemistry education programs, and to deal with common concepts found in these two disciplines employing an interdisciplinary approach. The study was realized by using analytical research model. Data of the study consists of Ministry of Education approved physics and chemistry textbooks for 9th, 10th, and 11th grades. Data were analyzed by content analysis method. As a result of the study, with the comparative examination of physics and chemistry course books, it was determined that the similarities are in the states of matter, heat, temperature, and energy subjects. In this respect, it is thought that determining common concepts especially in course books would be a solution to the lack of sufficient class hours, which is one of the most significant problems of the program